The Construction of Tangerang City’s Positive Image Through Instagram as New Media at the Peh Cun Dragon Boat Festival 2025 - Agung Putra Mulyana; Muhammad Irfan; Septyana Cahyadi (Journal of Innovative and Creativity, 2026)
The emergence of new media in our lives has made communication possible anytime, anywhere, and through any communication technology. Instagram has become a key tool in supporting public communication to shape an image. The purpose of this study is to analyze how the 2025 Peh Cun Festival dragon boat race was framed positively by the Instagram account @AboutTNG. This study uses a qualitative approach with Robert N. Entman's framing analysis method. The results show that the media has framed the 2025 Peh Cun Festival, which plays a role in shaping a positive image by upholding local cultural identity. The media emphasizes community participation, the value of diversity, and the government's full support for the continuity of traditions. Thus, this festival has been represented as a positive cultural practice that needs to be supported continuously.